Southern India in the Late Nineteenth Century : Volume l, Part ll-A and B: 1880s-1890s (Documents on Economic History of British Rule in India 1858-1947) - Bagchi, Amiya Kumar,; Bandopadhyay, Arun, (Brill | Manohar Publishers & Distributors, 2017)
This volume is part of the Project of Indian Council of Historical Research (ICHR) on documents pertaining to the economic history of British rule in India from 1858 to 1947. The present volume (divided into two parts A and B) on Southern India in the late nineteenth century roughly covers the broad economic history of Southern India during the 1880s and 1890s. It dwells on documents collected from a wide spectrum of human activity in Southern India. They included materials from diverse fields such as agriculture, forestry, population, public health, education and sanitation, in each of which the British Raj was involved in collecting information and directing the courses of development in more than one sense. A large part of Southern India was under raiyatwari settlement and an enormous number of documents were available touching on agricultural operations, agricultural appliances, material conditions of agricultural classes, population change, health and mortality, literacy and primary education, values of livestock and cattle diseases, production and export of cash crops, production and supply of food grains, distribution of waste lands, forests and reclamation of jungle lands, and scarcity and famines. These twenty years in the Madras Presidency immediately followed three developments earlier in the century. First, this is the period of the last stage of survey and settlement for what has been called the new ryotwari system. Second, the region experienced different measures of the government for the 'improvement' of the conditions of the people for which Raghavaiyanger spoke so eloquently. Finally, this was also a period of social conflict between the depressed classes like the Paraiyans and landowners of various categories. This volume touches on these crucial developments, and is thus expected to be a valuable source for students of the history of economic and human development of India.